1988
DOI: 10.1247/csf.13.425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tumor necrosis factor on cell growth and expression of transferrin receptors in human fibroblasts.

Abstract: ABSTRACT. Human recombinant tumor necrosis factor (TNF) stimulated the growth of confluent human fibroblasts (FS-4) in the presence of fetal calf serum. Epidermal growth factor (EGF) similarly stimulated cellular growth; however other mitogenic factors such as insulin, fibroblast growth factor, 12-Otetradecanoyl-phorbol-12-acetate and Ca2+ ionophore A23187 did not. The growth-stimulating action of TNF was not synergistic with the activity of EGF in the presence of serum. TNF induced a rapid increase in the bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…T insulin, fibroblast growth factor, and 12-0-tetradecanoyl-phorbol-12-acetate did not (Hori et al, 1988). In this present study, TGF-P was also found to increase the growth of FS-4 cells.…”
Section: Discussionsupporting
confidence: 43%
“…T insulin, fibroblast growth factor, and 12-0-tetradecanoyl-phorbol-12-acetate did not (Hori et al, 1988). In this present study, TGF-P was also found to increase the growth of FS-4 cells.…”
Section: Discussionsupporting
confidence: 43%
“…Reduction of TNF-induced PGE, synthesis by treatment with heparin was also observed when the experiment was carried out in the absence of fetal calf serum (Table 3, expt 2). The amounts of PGE, synthesized by cells in serum-free media were extremely low compared to that in media supplemented with fetal calf serum; previous observations have been made that fetal calf serum in the medium is an essential cofactor for TNF to exhibit certain types of biological functions (Hori et al, 1988;Sakagami et al, 1990;Martens et al, 1992).…”
Section: Surface-bound Type-11 Pla Is Involved In Pge Synthesismentioning
confidence: 93%
“…After several day's incubation, medium was removed and the cells were washed with CMF-PBS. Cell quantity was determined by the method of Hori et al (1988) with a minor modification. Cells were stained with 50 pl of 0.5% crystal violet per well in ethanoliwater (1:4) for 10 min and then washed with water.…”
Section: Automated Cell Countingmentioning
confidence: 99%